Two Informational Theories of Consciousness - Llontop, Diego (2017)
The paper presents two theories that seek to explain consciousness on the basis of the concept of information. Ortiz understands information as a material structure that shapes the human cerebral cortex, thus configuring consciousness, while Chalmers considers information as an “abstract space” not material but realizable in the physical, therefore, an element that could explain the ineffable character of consciousness. Both perspectives appear in a theoretical context in which classical materialism as hegemonic scientific image of the world shows an apparent insufficiency to account for the phenomenological aspect of consciousness.